Metastasis to the male breast from carcinoma of the urinary bladder: a rare case report (Journal of Pathology of Nepal, 2021)
Metastasis to the male breast is rarer than that of the female breast. Primary tumors of the urinary bladder to metastasize to the breast is more uncommon than other sites like lungs, ovary, or stomach. We report a case of a 59-year-old male patient with proven high-grade urothelial carcinoma of the bladder with lungs and anterior abdominal metastasis, presented with ulceroproliferative mass in the left breast nipple-areolar complex. Wide local excision was done and was sent for histopathological examination which showed neoplastic cells, morphologically resembling urothelial carcinoma. Immunohistochemical staining showed tumor cells positive for CK5/6, p63, GATA3, and Uroplankin, which confirmed the diagnosis and demonstrated the urothelial origin. There are no such cases reported to date in Nepal and very few cases are reported worldwide. Diagnostic accuracy depends on histologic analysis. Distinguishing between metastasis to the breast and primary breast tumor is important for therapy and prognosis.